Enhancing the Drug Release and Physicochemical Properties of Rivaroxaban via Cyclodextrin Complexation: A Comprehensive Analytical Approach - Cristina Solomon; Valentina Anuța; Iulian Sarbu; Emma Adriana Ozon; Adina Magdalena Musuc; Veronica Bratan; Adriana Rusu; Vasile-Adrian Surdu; Cătălin Croitoru; Abhay Chandak; Roxana Mariuca Gavriloaia; Teodora Dalila Balaci; et al. (Pharmaceuticals)
Background/Objectives: Rivaroxaban, an oral anticoagulant, shows poor aqueous solubility, posing significant challenges to its bioavailability and therapeutic efficiency. The present study investigates the improvement of rivaroxaban’s solubility through the formation of different inclusion complexes with three cyclodextrin derivatives, such as β-cyclodextrin (β-CD), methyl-β-cyclodextrin (Me-β-CD), and hydroxypropyl-β-cyclodextrin (HP-β-CD) prepared by lyophilization in order to stabilize the complexes and improve dissolution characteristics of rivaroxaban. Methods: The physicochemical properties of the individual compounds and the three lyophilized complexes were analysed using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray diffraction (XRD), and thermogravimetric analysis (TGA). Results: FTIR spectra confirmed the formation of non-covalent interactions between rivaroxaban and the cyclodextrins, suggesting successful encapsulation into cyclodextrin cavity. SEM images revealed a significant morphological transformation from the crystalline structure of pure rivaroxaban and cyclodextrins morphologies to a more porous and amorphous matrix in all lyophilized complexes. XRD patterns indicated a noticeable reduction in drug crystallinity, supporting enhanced potential of the drug solubility. TGA analysis demonstrated improved thermal stability in the inclusion complexes compared to the individual drug and cyclodextrins. Pharmacotechnical evaluation revealed that the obtained formulations (by comparison with physical mixtures formulations) possessed favorable bulk and tapped density values, suitable compressibility index, and good flow properties, making all suitable for direct compression into solid dosage forms. Conclusions: The improved cyclodextrins formulation characteristics, combined with enhanced dissolution profiles of rivaroxaban comparable to commercial Xarelto® 10 mg, highlight the potential of both cyclodextrin inclusion and lyophilization technique as synergistic strategies for enhancing the solubility and drug release of rivaroxaban.